Developing a collaborative learning framework for resilience in healthcare: a study protocol. Issue 8 (9th August 2021) - Haraldseid-Driftland, Cecilie; Aase, Karina; Wiig, Siri; Billett, Stephen
Abstract : Introduction: Resilience in healthcare (RiH) can be conceptualised as the adaptive capacities of a healthcare system that allow it to maintain the delivery of high-quality care during and after events that challenge, change or disrupt its activities. These adaptive capacities require collaborative learning and working, as the complexities of changes and challenges can rarely be addressed by individuals alone or single healthcare disciplinary knowledge. So, there is a need to understand how collaborative learning practices can be developed and supported both intra and inter disciplinary in healthcare. The aim of the study is to explore the relationship between collaborative learning, and resilience to establish a framework that supports the development and application of adaptive capacities across diverse healthcare contexts and levels. Collaborative learning is premised on learning as something that occurs continuously through everyday work in the healthcare systems as professionals engaging in clinical work, and interacting with other coworkers, patients and stakeholders making local adaptations in respond to needs. Method and analysis: The study applies a mixed methods design in a two-phased approach to explore and develop the relationship between collaborative learning and resilience. Phase One is exploratory using literature review, meta-synthesis, interviews and focus groups as data collection methods in empirical studies in different healthcare contexts. Phase Two uses participatory approach to develop and test a collaborative learning framework followed by an evaluation to appraise its utility using observation and focus groups as data collection procedures. Ethics and dissemination: Phase One of the study is approved by the Norwegian Centre for Research Data (reference no. 864334). The findings will be disseminated through scientific articles, presentations at international conferences and through social media and popular press. This includes establishing a set of learning tools for adaptive use, that is made publicly available in Open Access repositories.